Proceedings of the 10th ACM SIGCOMM Conference on Internet Measurement 2010
DOI: 10.1145/1879141.1879190
|View full text |Cite
|
Sign up to set email alerts
|

Understanding latent interactions in online social networks

Abstract: Popular online social networks (OSNs) like Facebook and Twitter are changing the way users communicate and interact with the Internet. A deep understanding of user interactions in OSNs can provide important insights into questions of human social behavior, and into the design of social platforms and applications. However, recent studies have shown that a majority of user interactions on OSNs are latent interactions, passive actions such as profile browsing that cannot be observed by traditional measurement tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(34 citation statements)
references
References 21 publications
(34 reference statements)
0
33
0
1
Order By: Relevance
“…Previous works have separately studied the evolution of the relative size of the network elements for specific OSNs (Flickr and Yahoo 360) [41], the growth of an OSN, and the evolution of its graph properties [24], [32], [33], [44], [46], [49], [57] or the evolution of the interactions between users [39], [54] and the user availability [28]. In this paper, instead of looking at a specific aspect, we perform a comprehensive analysis to study the evolution of different key aspects of G+, namely the system growth, the representative of the different network elements, the LCC connectivity and activity properties, and the level of information sharing.…”
Section: B Evolution Of Osn Propertiesmentioning
confidence: 99%
“…Previous works have separately studied the evolution of the relative size of the network elements for specific OSNs (Flickr and Yahoo 360) [41], the growth of an OSN, and the evolution of its graph properties [24], [32], [33], [44], [46], [49], [57] or the evolution of the interactions between users [39], [54] and the user availability [28]. In this paper, instead of looking at a specific aspect, we perform a comprehensive analysis to study the evolution of different key aspects of G+, namely the system growth, the representative of the different network elements, the LCC connectivity and activity properties, and the level of information sharing.…”
Section: B Evolution Of Osn Propertiesmentioning
confidence: 99%
“…Two earlier studies [16], [21] used clickstreams to analyze how users interact in OSNs and observed that 92% of user activities on OSNs are profile browsing, which implies that the majority of user interactions are latent interactions. Jiang et al [22] performed a detailed measurement and constructed latent interaction graphs. Similar to other work [10], we use the features reported by these empirical studies to generate user interactions for our simulations.…”
Section: A Experimental Setupmentioning
confidence: 99%
“…Specifically, the sets of read rates and write rates for all users are first generated from the power-law distribution with an exponent of 3.5 [22]. Following the statistics reported in [16], the ratio between the total read rate and total write rate is set at 0.92/0.08.…”
Section: A Experimental Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…du réseau Renren, le second réseau social numérique du pays, ainsi qu'aux historiques détaillés des visites de 61 000 utilisateurs du réseau Renren de l'Université de Pékin enregistrés sur 90 jours (Jing, Wilson et al, 2010). L'objectif était de mesurer la popularité relative de certains profils, la réciprocité des visites de profils et l'impact des mises à jour sur la popularité de certaines identités.…”
Section: Qui Est Mon Ami ?unclassified